OPTIMASI CHATBOT DALAM SISTEM PENGADUAN PELAYANAN PUBLIK BERBASIS ANDROID - Tholib, Abu; Andi, Moh syaiful; Sukron, Moh; Shudiq, Wali Ja'far; Hairani, Hairani; Guterres, Juvinal Ximenes (Insand Comtech : Information Science and Computer Technology Journal, 2025)
This study presents the development of an Android-based public service complaint application integrated with chatbot technology to improve service responsiveness. The system aims to facilitate community members in submitting complaints and receiving immediate responses through an interactive interface. A user-friendly mobile application was developed using the Kotlin programming language, and chatbot functionality was implemented via API integration to respond to frequently asked questions. The implementation followed the Waterfall model, encompassing stages of analysis, design, implementation, testing, and maintenance. Results show that the application effectively streamlines the complaint process, increases efficiency in complaint management, and enhances communication between the public and local government. The chatbot proved to be reliable in delivering relevant and timely responses, significantly reducing the time needed for initial interactions. This integration demonstrates the potential of artificial intelligence to support e-government services in rural setting